Measures of Spirituality/Religiosity (2018) - Büssing, Arndt (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The interest in the topic of spirituality as a more or less independent dimension of quality of life is continuously growing, and research questions are beginning to change as the field of religiosity changes, becoming more diverse and pluralistic. Addressing new topics in health research also relies on standardized questionnaires. The number of instruments intended to measure specific aspects of spirituality is growing, and it is particularly difficult to evaluate the new instruments. This Special Issue will focus on some of the established instruments (updating them to different languages and cultures), but will also describe the features and intentions of newly-developed instruments, which may potentially be used in larger studies to develop knowledge relevant to spiritual care and practice. This Special Issue will serve as a resource on the instruments used to study the wide range of organized religiosity, the individual experience of the divine, and an open approach in the search for meaning and purpose in life.